Innovations in Gong Bi painting by Xu Beihong: An Iconographic Study of Yugongyishan - Kang, Xiao; Wan Jamarul Imran, Wan Abdullah Thani (Woody International Publish Limited, 2024)
This study explores the transformative impact of Xu Beihong's reforms on traditional Gong Bi painting, with a focus on his renowned work "The Foolish Old Man Removes the Mountains." Gong Bi painting, an ancient and fundamental form of Chinese art dating back 2400 years, has undergone significant changes since the 20th century due to Western art influences. Xu Beihong, hailed as the pioneer of modern Gong Bi painting, integrated Western realism with traditional Chinese techniques to create a unique "East-meets-West" style. This research employs iconography to analyze the artistic elements, themes, and ideological context of Xu's work, highlighting its contribution to the evolution of Gong Bi painting. Through thematic analysis and case studies, the study reveals how Xu Beihong's innovative approach not only preserved the essence of Gong Bi painting but also adapted it to contemporary social and cultural landscapes, thus ensuring its relevance and sustainability in modern times. The findings underscore the critical role of individual artists in bridging cultural gaps and driving artistic innovation, ultimately contributing to the broader discourse on the fusion of Eastern and Western art traditions.